1998
DOI: 10.1016/s0735-1097(98)00311-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved left ventricular endocardial border delineation and opacification with OPTISON (FS069), a new echocardiographic contrast agent

Abstract: OPTISON appears to be a safe, well-tolerated echocardiographic contrast agent that is superior to ALBUNEX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
123
1
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(136 citation statements)
references
References 19 publications
4
123
1
5
Order By: Relevance
“…19 Several earlier studies investigated the influence of contrast enhancement on LV endocardial wall visibility and volume measurements using both 2DE and 3DE, as described schematically in table 2. [11][12][13][14][15][16][17][18][19][20][21][22]25 Among these, the results of two 2D studies using the ultrasound contrast agent Levovist are in line with the present study (a significant increase in LV volumes), effects that were ascribed to ultrasound contrast filling up intertrabecular space. 17,19 A similar study with EchoGen showed a small but significant decrease in LV end-diastolic volume, and no change in LV endsystolic volume and ejection fraction measurements.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…19 Several earlier studies investigated the influence of contrast enhancement on LV endocardial wall visibility and volume measurements using both 2DE and 3DE, as described schematically in table 2. [11][12][13][14][15][16][17][18][19][20][21][22]25 Among these, the results of two 2D studies using the ultrasound contrast agent Levovist are in line with the present study (a significant increase in LV volumes), effects that were ascribed to ultrasound contrast filling up intertrabecular space. 17,19 A similar study with EchoGen showed a small but significant decrease in LV end-diastolic volume, and no change in LV endsystolic volume and ejection fraction measurements.…”
Section: Discussionsupporting
confidence: 85%
“…Consistently, ultrasound contrast infusion led to improved endocardial visibility [11][12][13][14][15][16]18,21,25 and (when assessed) to improved volume measurement reproducibility. 17,19,21,22 In our patient group acoustic windows were good even without ultrasound contrast enhancement, but with the 3DE method we used, image reconstruction inherently causes a slight deterioration in image quality.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Thus, the medical and biomedical engineering communities have recognized that one factor that can contribute to reducing the death rate attributable to coronary heart disease is early detection and diagnosis (Asanuma et al 2004;Bruce et al 2004;Chen et al 2004;Dawson et al 2003;Takeuchi et al 2004;Yip et al 2003;Zhuang et al 2004). To this end, microbubble ultrasound (US) echogenic contrast imaging agents (CAs) were approved by the US Food and Drug Administration (FDA) for use in cardiology in the USA health care market (Al-Mansour et al 2000;Clark and Dittrich 2000;Cohen et al 1998;Malhotra et al 2000;Mulvagh et al 2000).…”
Section: Introduction and Literaturementioning
confidence: 99%